"Preparatory optimism among kindergarten students" (Journal of the College of Basic Education, 2024)
The current research aims to identify preparatory optimism among female students in the kindergarten department. The researchers adopted the scale of (Carver & Scheier 1985), and the scale in its final form consists of (12) items that were applied to a sample consisting of (200) female students in the kindergarten department in... College of Basic Education/Kindergarten Department, which was chosen randomly, and its validity and reliability were verified by extracting validity using the face validity method and construct validity. As for reliability, it was extracted using the retest method and the Cronbach coefficient, and the results concluded that the members of the research sample have predisposition optimism.